Association and distribution patterns of nipah (Nypa fruticans) in a degraded protected mangrove forest - SYAIFUL EDDY; NORIL MILANTARA; ANDI ARIF SETIAWAN; MIRNA TAUFIK; DEWI ROSANTI; SHAREN ANALIA DWINA PUTRI; RAHMAWATI RAHMAWATI (Society for Indonesian Biodiversity, 2024)
Abstract. Eddy S, Milantara N, Setiawan AA, Taufik M, Rosanti D, Putri SAD, Rahmawati. 2024. Association and distribution patterns of nipah (Nypa fruticans) in a degraded protected mangrove forest. Biodiversitas 25: 4525-4534. The invasion of nipah (Nypa fruticans) serves as an indicator of mangrove forest degradation that has occurred globally, impacting biodiversity. Therefore, understanding the population dynamics of nipah is essential for controlling its growth. This study aims to classify land cover types in the Air Telang Protected Forest (ATPF), analyze the association of nipah with other plants, and examine its distribution patterns. We employed a descriptive research method, utilizing Geographic Information Systems (GIS) for land cover change analysis, alongside field surveys to collect data on plant species associated with nipah. Drone photography was used to document nipah populations across various land cover types. Our findings revealed four land cover types in ATPF: primary forest, secondary forest, open area (shrub), and plantation, with 29 plant species associated with nipah. Nipah has spread across various land cover types through multiple mechanisms. We estimate that nipah will dominate nearly all degraded areas of ATPF and hinder the succession process if restoration efforts are not implemented promptly. However, with the right strategies, there is hope for successful restoration. This research contributes to understanding nipah's population dynamics, the implications of its dominance, and strategies for controlling its growth. In addition, this study is more widely useful for information on mangrove ecosystem management, ecological risk assessment, ecosystem restoration efforts, and conservation policy development.